The European Union´s Food Security Model and its External Dimension - Guinea, Mercedes (UNISCI Discussion Papers, 2014)
The European Union is the third human group in the planet, the first world food importer and the second food exporter. It is a global actor in food security, whose policies affect world agricultural trade and, consequently, food security policies of every State in the world, especially those dependent on imports for food supplies. In this paper we examine the EU food security model, established by the CAP, and its international aspects, food trade relations and development cooperation. This is important for the Maghreb countries, as European internal policies have an impact on international food availability and international market prizes. EU policies are a referent for its neighbouring countries because of close trade policies and cooperation ties.
Keywords: European Union; Common Agricultural Policy (CAP); agricultural trade policy; food security development cooperation.